2016
DOI: 10.3897/zookeys.549.6889
|View full text |Cite
|
Sign up to set email alerts
|

Thysanoptera-Terebrantia of the Hawaiian Islands: an identification manual

Abstract: An illustrated identification system is presented to 99 species and 49 genera in three families recorded from the Hawaiian Islands in the Thysanoptera suborder Terebrantia. Only seven (possibly eight) of these species are considered endemic, the remainder being adventive to these islands. The only previous study of Hawaiian Thysanoptera, by Zimmerman in 1948, included 47 Terebrantia species in 21 genera.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Recognition of this species is a high priority for quarantine entomologists, and the most closely similar species within Frankliniella seem to be crotalariae, intonsa, insularis and panamensis. The first of these is a pure yellow species that is probably host specific to the flowers of Crotalaria species, and although it is introduced to Hawaii (Mound et al 2016) it has not been reported in the world trade in horticultural products. The second species, intonsa, is widespread across the Northern hemisphere, and is commonly taken in quarantine.…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of this species is a high priority for quarantine entomologists, and the most closely similar species within Frankliniella seem to be crotalariae, intonsa, insularis and panamensis. The first of these is a pure yellow species that is probably host specific to the flowers of Crotalaria species, and although it is introduced to Hawaii (Mound et al 2016) it has not been reported in the world trade in horticultural products. The second species, intonsa, is widespread across the Northern hemisphere, and is commonly taken in quarantine.…”
Section: Introductionmentioning
confidence: 99%
“…The species status of G. ficorum remains uncertain for many years. Mound et al (2016) have suggested that G. ficorum is probably a form of G. uzeli , and morphological differences between different populations of these thrips can be due to different hosts and latitude. According to Brito et al (2010) , differences in chromosome number between G. uzeli (the cytotype A with n=13) and G. ficorum (n=15) as well as differences in chromosome morphology between G. uzeli (the cytotype B with n=4M+10SM+1A) and G. ficorum (n=4M+7SM+6T) indicate that both G. uzeli and G. ficorum are distinct species and that pericentric inversions led to the differentiation of their karyotypes.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Conventional insect taxonomy mostly relies on external morphology-based dichotomous keys for species delimitation. Several such resources are available for the identification of thrips specimens [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. However, species identification based on morphological characters is time-consuming as it involves processing of specimens, preparation of microscope slides, and magnification using a microscope, as well as expert morphological knowledge of the genera.…”
Section: Introductionmentioning
confidence: 99%